Handbook on Humanitarian Action Teaching in Cape Verde and Mozambique: Proceedings and Learnings - Pereira, Cláudia; Dragonas, Thalia; Pedroso, P.; Azevedo, J.; Freia, Alice; Ferrão, Arlete; Carvalho, Elga; Uaila, Evaristo; Sousa, Nardi (2024)
The Handbook provides the proceedings and learnings from the research experience of proposing a new vision for training in Humanitarian Action, focused on preparing humanitarians from countries affected by conflict and natural disasters. The first part focuses on the needs in the training of humanitarians. The second part focuses on the development of the HumAct project. The third part presents the teaching of the adapted and new modules of Humanitarian Action Humanitarian Action is taught at the universities of Cape Verde and Mozambique for the first time due to the HumAct project.